PERILAKU MEKANIS BETON MUTU TINGGI DENGAN PENAMBAHAN ABU SEKAM PADI DAN VISCOCRETE N-10 - Andi Yusra; Samsunan Mahmud (Inersia: Jurnal Teknik Sipil, 2019)
Generally in civil engineering, concrete structure used for the building of foundation, column, beam, plate or shell plate. The mentioned show how important are use of concrete in the field of civil engineering so that required by a circumstantial recognition hit the nature of substance of concrete . To yield the concrete with the high strength, use water or water cement ratio shall minimize with the consequence of concrete workmanship will become difficult because ofconcrete will become very jell, workability value become to minimize. The mentioned can beovercome by enhancing substance additive like superplasticizer. In this research used additives that is rice husk ash (RHA) with the addition of percentage of the weight of the cement 0 %, 5%, 8 %, 10 % and 15 %, it also used superplasticizer (viscocrete N-10) with the addition of percentage of the weight of the cement 1,5%. Concrete was designed with water cement ratio 0,30. Test were conducted was strength test of high strength concrete at 28 and 56 age days. Compressive strength test covered of concrete cylinder by 15 cm in diameter and 30 cm height. Amount of sample test was 30, where each variable used 3 samples. Result of high strength concrete compression test at age 28 days, show at addition of each rice husk ash, 0% yielding strength (55,46 MPA), 5% (50,55 MPA), 8% (48,29 MPA), 10% (53,19 MPA), and 15% (55,83 MPA). For the high strength concrete compression test at age 56 days, 0% yielding strength (59,80 MPA), 5% (63,38 MPA), 8% ( 56,02 MPA), 10% ( 58,47MPa), and 15% (59,98 MPA). Happen by strength addition 7,43% at age 56 day compared to strength at age 28 days with theaddition of rice husk ash equal to 15%.